Psychological suffering in the daily lives of women who have experienced sexual violence: a phenomenological study - Tatiane Herreira Trigueiro; Marcelo Henrique da Silva; Miriam Aparecida Barbosa Merighi; Deíse Moura de Oliveira; Maria Cristina Pinto de Jesus (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To understand the daily actions of women who have experienced sexual violence. Method: A qualitative study was conducted with 11 women who suffered sexual violence in southern Brazil. Their testimonies were obtained through phenomenological interviews conducted between October 2014 and April 2015. Results: The daily lives of women after suffering sexual violence were permeated by mental distress, translated into fear. This impacted their mental health by limiting their daily lives, especially social activities (work, school, sentimental, and sexual relations). To overcome the consequences of sexual violence, women sought support from family and friends and reintegration into the labor market and course of studies. Conclusion and implications for practice: Individual and group actions providing psychosocial and social support to women in situations of sexual violence are essential to help victims cope with the consequences of this experience.